Pipeline planning and construction field manual - Menon, E. Shashi (Gulf Professional Pub., 2011)
The objective of this book is to provide engineers with the necessary tools and techniques for formulating plans, designs, cost estimates and specifications for pipeline construction and field maintenance and modernization programs. Packed with easy to read and understand tables, pipeline schematics, bullet lists and ""what to do next"" checklists. This easy to use book covers the design, construction, and operation of onshore pipeline systems. The incorporate construction methods, commissioning, pressure testing, and start up into the design of a pipeline system. The focus is on pipeline r.
Keywords: Pipelines.; elektronické knihy; electronic books